Characterization of the composition, structure, and functional potential of bamboo rhizosphere archaeal communities along a chromium gradient - Zhang, Xiaoping; Li, Qiaoling; Zhong, Zheke; Huang, Zhiyuan; Bian, Fangyuan (Frontiers in Microbiology, 2024)
Bamboo can be used in the phytoremediation of heavy metal pollution.However, the characteristics of the bamboo rhizosphere archaeal community in Cr-contaminated soil under field conditions remain unclear.Here, we examined the rhizosphere soil archaeal communities of Lei bamboo (Phyllostachys precox) plantations along a Cr pollution gradient.The results revealed U-shaped relationships between Cr [total Cr (TCr) or HCl-extractable Cr (ACr)] and two alpha indices (Chao1 and Shannon) of archaea. We also established that high Cr concentrations were associated with a significant increase in the abundance of Thaumarchaeota and significant reductions in the abundances of Crenarchaeota and Euryarchaeota. The archaeal co-occurrence networks reduced in complexity with Cr pollution, decreasing the community's resistance to environmental disturbance.Nitrososphaeraceae_unclassified (two genera of Thaumarchaeota) were identified as keystone taxa. The community structure of soil archaeal communities was also found to be affected by TCr, ACr, pH, total organic C, and available nutrient (N, P, and K) concentrations, with pH being identified as the most reliable predictor of the archaeal community in assessed soils. These findings enhance our understanding of microbial responses to Cr pollution and provide a basis for developing more refined approaches for the use of bamboo in the remediation of Cr-contaminated 3 soils.